2017
DOI: 10.33043/ff.3.1.09-31
|View full text |Cite
|
Sign up to set email alerts
|

Cutting wedge: bacterial community diversity and structure associated with the cheese rind and curd of seven natural rind cheeses

Abstract: The microorganisms that inhabit cheese contribute greatly to the flavor and development of the final product. While the rind and curd microbiota have been characterized separately, there is limited information on how the structure and function of microbial communities in rinds and curds vary within and amongst cheeses. To better understand the differences in community structure and function between communities of cheese rinds and curds, we combined culture-based methods with culture-independent community profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Kamimura et al (2020) suggested that Lactococcus and Streptococcus are the most adapted genera regarding physicochemical conditions met during cheese production, ripening and storage. In Gruyere and Comte, a co-dominance of Streptococcus with Lactobacillus was already observed (Wei et al, 2016), but Lactobacillus was never in dominant position in our samples. During a study on Rushan cheese, Xue et al (2018) identified Acetobacter and Acinetobacter as (co-)dominant genera but, in the present study, these genera were either not detected or had a really low relative abundance (< 0.1%), respectively.…”
Section: Dominant Microbiotasupporting
confidence: 40%
See 2 more Smart Citations
“…Kamimura et al (2020) suggested that Lactococcus and Streptococcus are the most adapted genera regarding physicochemical conditions met during cheese production, ripening and storage. In Gruyere and Comte, a co-dominance of Streptococcus with Lactobacillus was already observed (Wei et al, 2016), but Lactobacillus was never in dominant position in our samples. During a study on Rushan cheese, Xue et al (2018) identified Acetobacter and Acinetobacter as (co-)dominant genera but, in the present study, these genera were either not detected or had a really low relative abundance (< 0.1%), respectively.…”
Section: Dominant Microbiotasupporting
confidence: 40%
“…Brevibacterium had an important relative abundance (> 10% at day-0 and end of shelf-life) in SRSC. Bacteria from these genera are rind colonizers, especially Brevibacterium linens, which is responsible for the red-orange color of SRSC rinds and was used as ripening starter in SRSC manufacture (Fox et al, 2017;Wei et al, 2016).…”
Section: Other Genera With Relative Abundance > 1%mentioning
confidence: 99%
See 1 more Smart Citation